2018
DOI: 10.1186/s13287-018-1013-z
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells from myelodysplastic and acute myeloid leukemia patients display in vitro reduced proliferative potential and similar capacity to support leukemia cell survival

Abstract: BackgroundMesenchymal stromal cells (MSCs) are an essential element of the bone marrow (BM) microenvironment, playing a crucial function in regulating hematopoietic stem cell proliferation and differentiation. Recent findings have outlined a putative role for MSCs in hematological malignancy development. So far, conflicting results have been collected concerning MSC abnormalities in acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). In particular, a considerable amount of evidence has been accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 59 publications
2
60
1
Order By: Relevance
“…Others have shown that AML-MSCs vs. ND-MSCs had decreased ability to support normal cobblestone area forming cells [56]. Other groups found no difference between AML-MSCs and ND-MSCs to support normal hematopoiesis in vitro [57]. Likewise, in this work, it was shown that AML-MSCs supported CFU-GMs more robustly that did ND-MSCs, but differential effects on blast apoptosis and survival were not demonstrated.…”
Section: Discussioncontrasting
confidence: 36%
“…Others have shown that AML-MSCs vs. ND-MSCs had decreased ability to support normal cobblestone area forming cells [56]. Other groups found no difference between AML-MSCs and ND-MSCs to support normal hematopoiesis in vitro [57]. Likewise, in this work, it was shown that AML-MSCs supported CFU-GMs more robustly that did ND-MSCs, but differential effects on blast apoptosis and survival were not demonstrated.…”
Section: Discussioncontrasting
confidence: 36%
“…Conversely, they may activate the innate and adaptive immune system (4,5). Studies have shown that MSCs undergo molecular and genetic changes contributing to disease progression (6). Other studies failed to show functional differences between MSCs from patients with MDS (MDS-MSCs) and healthy individuals (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that patient's BM‐MSCs do not harbour the same genetic abnormalities present in malignant cells. Common or disease‐specific genetic alteration in haematologic malignancies has not been identified 2‐5 . BM‐MSCs from patients with myelodysplastic syndrome (MDS) and acute myeloid leukaemia (AML) exhibit a wide range of functional and molecular alterations 4,6 .…”
Section: Introductionmentioning
confidence: 99%